Case report of sclerosing encapsulating peritonitis secondary to tuberculosis - A., Anandi; R., Preethy; R., Rani Suganya; S., Jothiramalingam (International Surgery Journal, 2021)
Sclerosing encapsulating peritonitis (SEP) is a visceral encapsulation syndrome of inflammatory origin, seen as an infrequent cause of intestinal obstruction in young patients. It is a condition characterised by complete encapsulation of small bowel loops by a fibrocollagenous membrane, leading to cocoon formation. Histologically, the membrane is composed mainly of organised fibrin, probably derived from the plasma exudation of peritoneal microvasculature. Clinical presentation is related to the development of altered gut motility, resulting in abdominal pain and features of intestinal obstruction. We here discussed about a young patient who presented with features of intestinal obstruction and diagnosed with SEP, secondary to abdominal tuberculosis and was then treated surgically. SEP as a cause of intestinal obstruction is a rare life threatening entity encountered in day to day practice. Definitive diagnosis of this condition is challenging in the pre-operative period and is usually missed and a high index of suspicion is required.